2004
DOI: 10.1111/j.1399-0039.2004.00161.x
|View full text |Cite
|
Sign up to set email alerts
|

Human leukocyte antigen‐A, ‐B, and ‐Cw polymorphism in a Berber population from North Morocco using sequence‐based typing

Abstract: Class I human leukocyte antigen (HLA) polymorphism was examined in a Berber population from North Morocco, named Metalsa (ME). All data were obtained at high-resolution level, using sequence-based typing. The most frequent alleles were: HLA-A*0201 and A*0101; HLA-B*44 (B*4403 and B*4402); B*0801 and the B*50 allele group (B*5001 and B*5002); HLA-Cw*0602; and Cw*07 group (Cw*070101, Cw*070102, Cw*0702, Cw*0704, and Cw*0706), and Cw*040101. The novel HLA-B*570302 allele was identified. It differs at position 486… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 45 publications
(44 reference statements)
6
37
1
Order By: Relevance
“…We therefore anticipate the need for customization of the HLA typing kits to increase the quality and resolution of HLA typing in the African population. The most frequent HLA-A alleles found in this study were HLA-A*30, -A*02, -A*23, and -A*68, with maximal frequency for A*30 (23.9%) as in most African population [8,10]. Interestingly, A*31 which is observed in African population at low frequencies, is absent in our sample [8,16].…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…We therefore anticipate the need for customization of the HLA typing kits to increase the quality and resolution of HLA typing in the African population. The most frequent HLA-A alleles found in this study were HLA-A*30, -A*02, -A*23, and -A*68, with maximal frequency for A*30 (23.9%) as in most African population [8,10]. Interestingly, A*31 which is observed in African population at low frequencies, is absent in our sample [8,16].…”
Section: Discussioncontrasting
confidence: 59%
“…In addition, few studies have been conducted in populations from the sub-Saharan area [8 -10]. In fact, only four populations have been extensively studied in subSaharan Africa: the Zulu from South Africa [11], the Luo from Kenya [8], the Fulani from Burkina Faso [9], and the Maltasa Berber from the city of Nador, Marroco [10].…”
Section: Introductionmentioning
confidence: 99%
“…In this investigation, the reactivity lot 3 of Moroccan IVIg (Table 5) [5]. The density of the antibodies as assessed by the levels of MFI for B*0801, B*5001, Cw*0602 and Cw*0702 are high parallel with their high frequency distribution.…”
Section: Unique Profile Of Anti-hla-i Igg In Ivig On Ibeadsmentioning
confidence: 81%
“…Studies examining HLA-I types in Casablanca, the largest region of Morocco, reported that the most frequent types were HLA-A2 (21%), -A1 (11%), -A3 (10%), -B44 (11.4%), -B50 (9.9%), -B5 (8.5%) and -B35 (6.5%) [4]. Similarly, in the Amazigh ethnic group, the most frequent alleles were HLA-A*0201, A*0101; HLA-B*4403, B*4402, B*0801, B*5001, B*5002; HLA-Cw*0602, Cw*070101, Cw*070102, Cw*0702, Cw*0704, and Cw*0706, Cw*040101 [5]. Molecular typing of HLA-II in Amazigh group (Souss) revealed high frequencies for DRB1*0701, DRB1*0301, DQA1*0501, DQA1*0201, and DQB1*0201 [6].…”
Section: Introductionmentioning
confidence: 99%
“…24 Sub-Saharan introgression into Europe could have been the result of indirect contact of Europeans with North Africans already admixed with Sub-Saharan populations. 25,26 This two-step SubSaharan introgression into Europe could be an interesting subject of future research validated through demographic simulations.…”
Section: Discussionmentioning
confidence: 99%